The effectiveness of mindful parenting in improving the psychological well-being of parents of preschool students with special needs - Indrawati, Triana (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background: Parents of young children with special needs often face unique psychological challenges. The ex-Pekalongan Residency area, encompassing Pekalongan City and Batang Regency, is the focus of this study.Aim: This research evaluates the effectiveness of a mindful parenting program designed to improve the psychological well-being of these parents.Method: A total of 30 parents from PAUD Anggun Poncol (Pekalongan City), TK Negeri Pembina Limpung, and TK Mutiara Hati Brayo (both in Batang Regency) participated. These individuals were selected through purposive sampling and assessed using a 36-item psychological well-being scale in a quasi-experimental quantitative study. The paired sample t-test was utilized for data analysis.Results: Initial assessments showed an average psychological well-being score of 49.5. After the mindful parenting program, this score increased to 85.55, indicating significant improvement. The mean difference in well-being scores was 36.05, with a standard deviation of 8.35.Conclusion: The mindful parenting program effectively enhanced the psychological well-being of parents with early childhood education students who have special needs in the ex-Pekalongan Residency. The substantial increase in well-being scores post-intervention confirms its beneficial impact.